Can Digitalization Levels Affect Agricultural Total Factor Productivity? Evidence From China - Fu, Wenqiang; Zhang, Rongwu (Frontiers in Sustainable Food Systems, 2022)
The agricultural sector faces a food crisis and major challenges in green and sustainable development, and digital technology is an important countermeasure. In this paper, “digital technology” is used as a keyword to construct a regional digitalization level indicator. China's provincial panel data from 2013 to 2020 are adopted as samples to explore the impact of regional digitalization levels on agricultural total factor productivity and its mechanism. The study found the following: (1) Regional digitalization can significantly raise agricultural total factor productivity. (2) Regional digitalization can significantly raise agricultural total factor productivity in economically underdeveloped areas but not in economically developed areas. (3) The mitigation of factor market distortion and large-scale production can strengthen the role of regional digitalization in raising agricultural total factor productivity.